The Effect of TGF-β3 and IL-1β on L-Type Voltage-Operated Calcium Channels and Calcium Ion Homeostasis in Osteoarthritic Chondrocytes and Human Bone Marrow-Derived Mesenchymal Stem Cells During Chondrogenesis - Anastasiia Shelest; Aidas Alaburda; Raminta Vaiciuleviciute; Ilona Uzieliene; Paulina Bialaglovyte; Eiva Bernotiene (Pharmaceutics)
Background: Transforming growth factor-β (TGF-β) and interleukin 1β (IL-1β) are key regulators of the chondrogenic differentiation, physiology and pathology of cartilage tissue, with TGF-β promoting chondrogenesis and matrix formation, while IL-1β exerts catabolic effects, inhibiting chondrogenesis and contributing to cartilage degradation. Both cytokines alter the intracellular calcium ion (iCa2+) levels; however, the exact pathways are not known. Objectives: This study aimed to evaluate the impact of TGF-β3 and IL-1β on calcium homeostasis in human bone marrow-derived mesenchymal stem cells (hBM-MSCs) and chondrocytes during chondrogenesis. Results: TGF-β3 increased iCa2+ levels in both hBM-MSCs and chondrocytes. Furthermore, TGF-β3 increased the functional activity of L-type voltage-operated calcium channels (L-VOCCs) in hBM-MSCs but not in chondrocytes. TGF-β3 and IL-1β reduced L-VOCCs subunit CaV1.2 (CACNA1C) gene expression in chondrocytes. In hBM-MSCs, TGF-β3 and IL-1β increased SERCA pump (ATP2A2) gene expression, while in chondrocytes, this effect was observed only with TGF-β3. Conclusions: TGF-β3 increases iCa2+ both in osteoarthritic chondrocytes and hBM-MSCs during chondrogenesis. In hBM-MSCs, TGF-β3-mediated elevation in iCa2+ is related to the increased functional activity of L-VOCCs. IL-1β does not change iCa2+ in osteoarthritic chondrocytes and hBM-MSCs; however, it initiates the mechanisms leading to further downregulation of iCa2+ in both types of cells. The differential and cell-specific roles of TGF-β3 and IL-1β in the calcium homeostasis of osteoarthritic chondrocytes and hBM-MSCs during chondrogenesis may provide a new insight into future strategies for cartilage repair and osteoarthritis treatment.